Numerical modelling of pressure rise combustion for reducing emissions of future civil aircraft - Materano Blanco, Gilberto Ignacio (Cranfield University, 2014)
This work assesses the feasibility of designing and implementing the wave rotor (WR), the pulse detonation engine (PDE) and the internal combustion wave rotor (ICWR) as part of novel Brayton cycles able to reduce emissions of future aircraft. The design and evaluation processes are performed using the simplified analytical solution of the devices as well as 1D-CFD models. A code based on the finite volume method is built to predict the position and dimensions of the slots for the WR and ICWR. The mass and momentum equations are coupled through a modified SIMPLE algorithm to model compressible flow. The code includes a novel tracking technique to ensure the global mass balance. A code based on the method of characteristics is built to predict the profiles of temperature, pressure and velocity at the discharge of the PDE and the effect of the PDEs array when it operates as combustion chamber of gas turbines. The detonation is modelled by using the NASA-CEA code as a subroutine whilst the method of characteristics incorporates a model to capture the throttling and non-throttling conditions obtained at the PDE's open end during the transient process. A medium-sized engine for business jets is selected to perform the evaluation that includes parameters such as specific thrust, specific fuel consumption and efficiency of energy conversion. The ICWR offers the best performance followed by the PDE; both options operate with a low specific fuel consumption and higher specific thrust. The detonation in an ICWR does not require an external source of energy, but the PDE array designed is simple. The WR produced an increase in the turbine performance, but not as high as the other two devices. These results enable the statement that a pressure rise combustion process behaves better than pressure exchangers for this size of gas turbine. Further attention must be given to the NOx emission, since the detonation process is able to cause temperatures above 2000 K while dilution air could be an important source of oxygen.
Keywords: Wave Rotor; Pulse Detonation Engine; Internal Combustion Wave Rotor; Gas turbine; Performance